2008
DOI: 10.1136/vr.163.13.386
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the mortality of pigs being transported to slaughter

Abstract: A multilevel logistic regression model was used to identify and quantify the effects of factors affecting the mortality of pigs being transported to slaughter under commercial conditions. A survey of 739 journeys to 37 slaughterhouses in five eu countries was carried out, and information potentially related to the welfare and mortality of the pigs and the number of injuries were recorded. The average temperature during the journey, its duration, the average loading time per pig, the recorded injuries, fasting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 21 publications
(25 reference statements)
3
58
0
4
Order By: Relevance
“…of animals loaded; x2=travelled distance (km). The data were analyzed using the SAS Proc Logistic software package (SAS, (Guàrdia et al, 2004) and the risk of pig mortality after transport to the slaughterhouse (Averos et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…of animals loaded; x2=travelled distance (km). The data were analyzed using the SAS Proc Logistic software package (SAS, (Guàrdia et al, 2004) and the risk of pig mortality after transport to the slaughterhouse (Averos et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The use of an electrical goad increased heart rate over a short time interval, by up to 200 bpm, partly because the pigs were running to avoid the electric shock (Küchenmeister et al, 2005). Averós et al (2008) reported in their survey on mortality of pigs in five EU countries that the risk of mortality increased as the average time taken to load them decreased. Driessen et al (2008) studied the influence of olfactory substances on heart rate and lying behavior of pigs during transport simulation.…”
Section: Facilities and Proceduresmentioning
confidence: 99%
“…Based on meat quality and transport losses they concluded that transport should not take more than 16 h in order to improve carcass quality and animal welfare. Assessment of mortality risk factors revealed that average temperature is more important than the duration of the journey (Averós et al, 2008).…”
Section: Water and Feeding Intervals Journey Times And Resting Periodsmentioning
confidence: 99%
See 2 more Smart Citations